General practitioners' views on quality specifications for "outpatient referrals and care contracts". Issue 6797 (3rd August 1991) - Bowling, A; Jacobson, B; Southgate, L; Formby, J
Abstract : OBJECTIVE--To ascertain general practitioners' views about which quality specifications should be included in contracts for hospital care. DESIGN--In depth interview study and postal survey. SETTING--General practitioners in City and Hackney Health District. SUBJECTS--Fourteen doctors were interviewed in depth; 77 of 131 doctors (59%) returned postal questionnaires. MAIN OUTCOME MEASURE--Rating of listed quality specifications. RESULTS--The most popular items which doctors thought should be included in contracts by April 1991 related to the availability of patients' notes in outpatient clinics, respect shown to general practitioners in telephone communications with hospital doctors, supply of medicines after discharge, patient management plans for general practitioners, the earlier arrival of discharge slips, the type of hospital doctor to see new outpatients, and the unnecessary duplication of investigations. CONCLUSIONS--A high premium was attached by general practitioners to effective organisation, effective communication between primary and secondary sources of care, and effective communication with patients.